2023
DOI: 10.1101/2023.01.18.524533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Globoside and the mucosal pH mediate parvovirus B19 entry through the epithelial barrier

Abstract: Parvovirus B19 (B19V) is transmitted primarily via the respiratory route, however, the mechanism involved remains unknown. B19V targets a restricted receptor expressed in erythroid progenitor cells in the bone marrow. However, B19V shifts the receptor under acidic conditions and targets the widely expressed globoside. The pH-dependent interaction with globoside may allow virus entry through the naturally acidic nasal mucosa. To test this hypothesis, MDCK II cells and well-differentiated human airway epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
3
1
0
Order By: Relevance
“…However, acidic niches in the body, such as the nasal mucosa, can become potential targets for B19V. In line with this, we demonstrated that the upper respiratory epithelium expresses globoside and allows virus attachment and transcytosis across the airways exclusively under the acidic pH of the nasal mucosa [23].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, acidic niches in the body, such as the nasal mucosa, can become potential targets for B19V. In line with this, we demonstrated that the upper respiratory epithelium expresses globoside and allows virus attachment and transcytosis across the airways exclusively under the acidic pH of the nasal mucosa [23].…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with this notion, in a previous study we found that binding of B19V to globoside expressed on airway epithelial cells exposed to acidic conditions was required and sufficient to induce membrane invagination leading to virus internalization [23].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations